2023
DOI: 10.1002/jso.27206
|View full text |Cite
|
Sign up to set email alerts
|

A novel predictive model for postoperative delirium using multiple geriatric screening factors

Abstract: Objectives The purpose of this study was to develop a new composite score to accurately predict postoperative delirium (POD) after major urological cancer surgery. Methods Our retrospective analysis included, in total, 449 consecutive patients who experienced major urological cancer surgery and a preoperative geriatric functional assessment at our institution (development cohort). Geriatric functional assessments included Geriatric 8, Instrumental Activities of Daily Living, and mini‐cognitive assessment instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…A total of 48 articles were included in this study (Table 1), of which 39 (81.25%) studies were cohort, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][39][40][41][42][45][46][47][49][50][51]54,57,[59][60][61][62][63][64][65][66][67][68] and 8 (16.6%) were randomized clinical 38,43,44,48,52,53,55,58 trials (one article excluded in the late stage as it was retracted in the publisher journal).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 48 articles were included in this study (Table 1), of which 39 (81.25%) studies were cohort, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][39][40][41][42][45][46][47][49][50][51]54,57,[59][60][61][62][63][64][65][66][67][68] and 8 (16.6%) were randomized clinical 38,43,44,48,52,53,55,58 trials (one article excluded in the late stage as it was retracted in the publisher journal).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-three studies included samples comprised of patient with gastrointestinal (GI) cancers, 22,24,26,[28][29][30][31][32][33]35,36,39,40,42,49,50,53,55,57,58,60,65,67 seven with urological cancers, 25,27,[45][46][47]62,68 nine on various cancers, 34,38,43,48,51,52,56,59,64 three with head and neck cancers, 21,23,41 and one with gynecological, lung, oral, and brain (tumor) cancers, respectively. Of the 48 studies, 39 [21][22][23][24][25][26][27][28]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mini‐cognitive assessment instrument (Mini‐Cog), 80 a simple screening tool consisting only of a three‐word playback and clock drawing, has diagnostic capabilities similar to MMSE 81 and is recommended by the SIOG task force for use in screening 73 . The authors also reported that the patients with Mini‐Cog <3 had a higher risk of delirium after major urologic surgery 82,83 or transurethral surgery under spinal anesthesia 84 . The insertion of a urinary catheter can increase the risk of delirium, 85 as shown by in vivo experiments with mice exhibiting delirium‐like behavior after catheterization 86 .…”
Section: Cognitive Abilitymentioning
confidence: 99%